Self-regulated Learning for High School Students in Biology Lessons through the Problem-Based Learning Model - Gamar Binti Non Shamdas (Journal of Innovation in Educational and Cultural Research, 2023)
The ability to acquire knowledge and skills through systematic and deliberate monitoring of one's behavior is not evenly distributed among each student. Quantitative research using quasi-experimental methods aims to findthe effect of PBL on self-regulated learning, the effect of PBL on self-regulated learning based on gender, and to identify self-regulated learning for high school students based on indicators. The research design was a Posttest Only Control-Group Design carried out on Class XI students at a high school in Palu City with a population of 7 classes. Self-regulated learning data were obtained through questionnaires that were distributed to the experimental and control classes after learning was complete. Data were analyzed using an independent t-test and analysis of each indicator of self-regulated learning using the percentage formula. The study finds that self-evaluation is the most important indicator of self-regulated learning and that learning using the PBL model has a significant impact on student self-regulated learning based on gender and in comparison to conventional learning.It is recommended to apply the PBL model to learning in schools in Indonesia in particular to increase the ability of each student to carry out independent learning.